Role Of The Center For Abandonment Of Property Law To Safeguard Assets Subsidiaries Who Still Under Age - Agustina Suryaningtyas (Jurnal Daulat Hukum, 2018)
For those who are not competent to act in a legal act such as minors and people who are in wardship, in legal actions both in and out of court must be represented by a person appointed by the trial judge, that is able to parent, guardian or sycophants. Duties as guardian or caretaker are very spacious and are at risk for problems associated with wealth, so that the necessary role of an institution or agency in charge of overseeing the implementation of trusteeship and guardianship. Parents, family and society are responsible for protecting and maintaining human rights in conformity with the obligations imposed by law. Similarly, in view of the protection of children, the state and the government is responsible for providing facilities and accessibility for children, especially in ensuring optimal growth and development and focused. Heritage Hall is one of the Technical Unit within the Ministry of Justice and Human Rights of the Republic of Indonesia has the duty and obligation to protect human rights. Especially in the field of personal right person for Judge's decision can not run their own interests by the legislation in force. Ranking Universal Heritage as guardian watchdog is still needed, and it is possible to apply to all Indonesian citizens, thus Orphan peningalan can act in the national interest to provide legal protection for children who are under guardianship committed by Indonesian.Keywords: Heritage Office; Minors; Guardianship.